Gestational and Perinatal Exposure to Diazinon Causes Long-lasting Neurobehavioral Consequences in the Rat - Hawkey, Andrew (Toxicology, 2019)
Diazinon is a widely-used organophosphate pesticide. Pulsatile exposure to diazinon during neonatal development has previously been shown cause long-term neurobehavioral impairments in rats. However, the effects of chronic low concentration exposures during perinatal development remain unclear. This experiment evaluated such effects in Sprague-Dawley rats by implanting osmotic pumps in breeder females prior to conception (N=13–15 litters per condition) which then delivered chronic, zero order kinetic low-level infusions of 0, 114 or 228 ug/day of diazinon throughout pregnancy. One male and one female from each litter was assessed with a battery of behavioral tests that continued from four weeks of age into adulthood. Litter was used as the unit of variance for the analysis of variance test of significance, with sex as a within litter factor. Diazinon treatment condition was the between subjects factor and time or sessions were repeated measures. Chronic diazinon exposure from pre-mating until the neonatal period caused a significant (p<0.05) increase in percent of time spent on the open arms of the elevated plus maze, an index of risk-taking behavior. Gestational and lactational diazinon exposure also caused a significant (p<0.05) degree of hyperactivity in the Figure-8 apparatus during adolescence, specifically affecting the early part of the hour-long test session. This effect had dissipated by the time the rats reached adulthood. Diazinon exposure also caused a significant impairment in novel object recognition, a test of cognitive function. Offspring exposed to 228 ug/day diazinon (p<0.05) showed significantly less preference for the novel vs. familiar object than controls during the first five minutes of the novel object recognition test.